Preparation and Study Ag Nanoparticles via PLAL Technique: Influence of Different Number of Pulses - Thuraya Yarb Sabri; Saif Khalel Jasim; Ammar Ayesh Habeeb; Awatif Saber Jasim (International Journal of Nanoelectronics and Materials (IJNeaM), 2024)
Using a quick, easy, and effective one-step synthesis method called Q-switched neodymium-doped yttrium aluminum garnet (Nd:YAG)-pulsed laser ablation in liquid (PLAL), silver nanoparticles (NPs) are physically created. By using a pulsed laser at 532 nm to vaporize a metallic target (in this case, silver) submerged in deionized water, silver colloidal solutions are separately created. Laser parameters pulse of number (100, 200, and 300 pulse/sec) with constant ablation energy 500 mJ. The cubic crystalline structure of Ag particles was revealed by XRD, along with the formation of a pure cubic crystal structure of Ag particles and another cubic crystal structure attributed to AgO particles. The subsequent FESEM images showed the formation of highly spherical crystals (mean diameter 25.003 nm, 24.43 nm, and 9.75 nm ). UV-Vis analysis reveals the absorption band of Ag NPs at (407, 406, and 404 nm), and the energy gap was (2.74, 2,79, and 2.95 eV ) respectively. The diagnosis of spherical colloidal Ag-NPs was approved by FESEM, and the PL spectra show two peaks at 320 and 639 nm, confirming the purity of the produced Ag-NPs. It is clear that the possibility of using the prepared nanoparticle in optoelectronics applications such as optical detectors, solar cells, and optical sensors.